GEORGIA: ENERGY POLICY - CHOMAKHIDZE, Demur (CENTRAL ASIA AND THE CAUCASUS, 2007)
This article describes the main vectors in Georgia’s state policy in the energy sector during the years of independence after the Rose Revolution and calculates the forecast indices and anticipated results of the development of the power industry until 2015. The formation and implementation of energy policy in Georgia is of special importance. There are objective reasons for this. The country customarily experiences a shortage of fuel and energy resources (FER). The situation became particularly aggravated after the country gained its independence. It be-came clear that a concise energy policy was essential not only to guarantee the country’s economic se-curity, but also to preserve its statehood. Since the very first days of independence, the country has had to come to terms with the situation that has developed, reconsider its limited material-financial and nat-ural energy resources, and create and implement an optimal model of its energy policy. According to the Georgian Constitution, an integrated energy system is among the facilities that are specifically managed by the highest state bodies.1 This means that the government has a particular responsibility in this issue. In compliance with the Georgian Law on Electric Power and Natural Gas, the Ministry of Ener-gy is drawing up the main vectors of state policy in the country’s energy sector, and it also puts these vectors into practice after they are approved by parliament.2 The concept “energy policy” implies a general course and system of measures in energy manage-ment. It includes defining the relevant areas in the processes going on in the country in keeping with the goals and tasks it faces. This concept reveals the country’s dependence on the energy complex. During the years of independence, the Georgian Ministry of Energy has drawn up several projects, conceptions, and main vectors of the country’s energy policy, but until 2006 none of them were ap-proved by the parliament.